KAJIAN KUALITAS AIR SUMUR PADA PERMUKIMAN BARU KELURAHAN JEKAN RAYA PALANGKA RAYA SERTA KAITANNYA DENGAN SUMBER AIR BERSIH WARGA - Marvin Horale Pasaribu; Tety Wahyuningsih Manurung; Mokhamat Ariefin (Jurnal Bakti untuk Negeri, 2023)
Clean water is a fundamental requirement for human life. People depend on easy and safe access to clean water to fulfill their daily needs. Palangka Raya is the capital city of Central Kalimantan Province and is also affected by the process of moving the National Capital City (IKN) to Kalimantan. The population growth rate is increasing every year, accompanied by an increasing number of settlements in Palangka Raya. Its area is mostly peatland, so its surface water affects the well water used by many newly established settlements as a source of clean water for its citizens. In this service, the method is sampling residential healthy water, analyzing water samples, and counseling residents. Water analysis shows that healthy water is quite suitable for hygiene and sanitation purposes but not for consumption according to clean water quality standards based on Permenkes No. 32 of 2017. The results of the socialization showed an increase in the level of understanding of residents on healthy water quality. This activity is expected to help the government improve the Casadova residents' health. It is expected to increase the knowledge and awareness of residents about the proper use of well water and maintaining the quality of healthy water.